1997
DOI: 10.1021/la970780y
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Quenching Studies of the Interaction of a Pyrene-Labeled Polyelectrolyte with Quencher-Carrying Oppositely Charged Micelles

Abstract: The interaction between poly(sodium 2-(acrylamido)-2-methylpropanesulfonate) labeled with 1 mol % pyrene (PyPAMPS) and mixed micelles of hexaethylene glycol n-dodecyl monoether (C12E6) and n-hexadecyltrimethylammonium chloride (CTAC), in which N,N-dimethylaniline (DMA) was solubilized, was studied by steady-state and time-dependent fluorescence quenching by varying the mole fraction of CTAC (Y) in the mixed micelle. At Y < 0.05, fluorescence quenching is essentially dynamic, arising from collisional encounters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 29 publications
1
56
0
Order By: Relevance
“…Fluorescence techniques offer, in principle, considerable insight into such questions. 26,27 Although fluorescence probes have been frequently used to study polymersurfactant interactions, 28 the goal of such investigations has been the determination of the aggregation number of bound (i.e., versus free) micelles. A different application of fluorescence to polyelectrolyte-colloid interactions was presented in our investigation of the fluorescence behavior of a pyrene-tagged polyanion arising from its photophysical interaction with tryptophan residues in lysozyme.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescence techniques offer, in principle, considerable insight into such questions. 26,27 Although fluorescence probes have been frequently used to study polymersurfactant interactions, 28 the goal of such investigations has been the determination of the aggregation number of bound (i.e., versus free) micelles. A different application of fluorescence to polyelectrolyte-colloid interactions was presented in our investigation of the fluorescence behavior of a pyrene-tagged polyanion arising from its photophysical interaction with tryptophan residues in lysozyme.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of quenching upon increase in σ or decrease in κ was investigated by steady-state and timedependent fluorescence spectroscopy to provide insight into the dynamics of polyelectrolyte-micelle association. 26, 27 The behavior of fluorescence-labeled polyelectrolytes may be perturbed by the physicochemical properties of the label. Thus, turbidimetric, light scattering, and fluorescence studies revealed that the interaction of pyrene-labeled poly(sodium 2-(acrylamido)-2-methylpropanesulfonate) (PAMPS) with mixed micelles of n-dodecyl hexa(oxyethylene) glycol monoether (C 12 E 6 ) and cetyltrimethylammonium chloride (CTAC), although predominantly driven by electrostatic forces, occurred preferentially with pyrene sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36] Among these methods, fluorescence techniques are expected to provide a powerful tool to gain insight into the dynamics of polyelectrolyte-micelle interactions. Recently, we used a pyrene-labeled polyanion in conjunction with quencher-carrying mixed micelles to characterize the microscopic polyelectrolytemicelle phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we used a pyrene-labeled polyanion in conjunction with quencher-carrying mixed micelles to characterize the microscopic polyelectrolytemicelle phase transition. [33][34][35][36] The intensity of the polyelectro- † Part of the special issue "Noboru Mataga Festschrift". ‡ Current address: Shiseido Basic Research Center, 2-2-1 Hayabuchi, Tsuzuki, Yokohama 224-8558, Japan…”
Section: Introductionmentioning
confidence: 99%